Pericardiectomy in pregnancy. Issue 5 (September 1970) - Richardson, P. M.; Le Roux, B. T.; Rogers, N. M. A.; Gotsman, M. S.
Abstract : Details are presented which relate to a patient in whom constrictive pericarditis developed during pregnancy. Successful pericardiectomy was performed at 24 weeks gestation and a normal infant was delivered at term. The results of medical and surgical treatment of cardiac patients during pregnancy, the results of pericardiectomy, and the risk to the foetus are discussed.